2010
DOI: 10.1109/tpc.2010.2046088
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Roles, Socioemotional Communication Strategies, and Technology Use of Irish and US Students in Virtual Teams

Abstract: Abstract-Global virtual teams provide numerous benefits both for corporations employing virtual organizational forms and for individual teams and team members.However, virtual collaboration also presents some well-recognized challenges. A growing body of research has examined the process of virtual teaming and the challenges inherent in that process. This study seeks to address some of the gaps in the existing literature. Specifically, it examines leadership roles, socio-emotional Development to undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
(22 reference statements)
3
25
0
Order By: Relevance
“…An increasing body of research has demonstrated the benefits of having students learn international professional communication by working in CCVTs, linked through the Internet (Flammia, 2005(Flammia, , 2012Flammia, Cleary, & Slattery, 2010;Gerritsen & Verckens, 2006;Goby, 2007;Jarvenpaa & Leidner, 1999;Stärke-Meyerring, Duin, & Palvetzian, 2007). Our own publications have depicted the basics of international collaborations between students in technical communication courses in North America and students in translation courses in Europe (Humbley et al, 2005;Mousten et al, 68 MAYLATH ET AL. 2008; Mousten, Humbley, Maylath, & Vandepitte, 2012;Mousten, Maylath, Humbley, Scarpa, Livesey, & Vandepitte, 2010a;Mousten, Maylath, Vandepitte, & Humbley, 2010b).…”
Section: Managing Complexity: a Technical Communication Translation Cmentioning
confidence: 97%
“…An increasing body of research has demonstrated the benefits of having students learn international professional communication by working in CCVTs, linked through the Internet (Flammia, 2005(Flammia, , 2012Flammia, Cleary, & Slattery, 2010;Gerritsen & Verckens, 2006;Goby, 2007;Jarvenpaa & Leidner, 1999;Stärke-Meyerring, Duin, & Palvetzian, 2007). Our own publications have depicted the basics of international collaborations between students in technical communication courses in North America and students in translation courses in Europe (Humbley et al, 2005;Mousten et al, 68 MAYLATH ET AL. 2008; Mousten, Humbley, Maylath, & Vandepitte, 2012;Mousten, Maylath, Humbley, Scarpa, Livesey, & Vandepitte, 2010a;Mousten, Maylath, Vandepitte, & Humbley, 2010b).…”
Section: Managing Complexity: a Technical Communication Translation Cmentioning
confidence: 97%
“…Second, it specifically measured perceptions of difficulty directly related with the virtual aspect -distant coordination and administration. Students rated, on a scale of 1 (minimal level) to 5 (maximum level), their perceptions of difficulty arising from 1) coordination of time zones (Sutanto, Kankanhalli & Tan, 2011), 2) differences in personal abilities (Liu, Magjuka & Lee, 2008), 3) coordination of work (Flammia, Cleary & Slattery, 2010;Liu, Magjuka & Lee, 2008), 4) electronic-virtual means of communication (Sutanto, Kankanhalli & Tan, 2011), 5) lack of authority and clear leadership (Caligiuri & Tarique, 2012;Flammia, Cleary & Slattery, 2010;Jonsen & Maznevski, 2010;Maznevski & DiStefano, 2000), and 6) differences in motivation of members (Liu, Magjuka & Lee, 2008). It was hypothesized that the experimental group, after completing the X-Culture project, would report higher levels of perceived difficulties related with these aspects of the GVT.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Students have ample opportunities for experiential learning when participating in study abroad and when engaged in international service-learning. However, students who are unable to study abroad can benefit from assignments requiring them to collaborate with diverse others (Flammia, Cleary, & Slattery, 2010;Patterson, Carrillo, & Salinas, 2012;Sklad, Friedman, Park, & Oomen, 2016). This paper describes a semester-long project undertaken by a technical communication class to write a guide to international research for undergraduate students at the UCF.…”
Section: Student Involvement In Internationalization Effortsmentioning
confidence: 99%